PERANAN FILSAFAT ILMU TERHADAP ILMU EKONOMI DAN PENGEMBANGAN PARA SARJANANYA - Nasrullah, Yazid (Jurnal Ekonomi & Studi Pembangunan, 2003)
As a mother of sciences, epistemology contributes in improving economic. By studying epistemology economists be realize that they have some limitations in soliving socioeconomic problems. It make them no to be an arrogant but a numble intellectual.